Peace for Sale: An Analysis of IKEA’s Efectos Colaterales Advertising Campaign in Spain - Naranjo Franco, Gerardo; Subin, Paul (SAGE Publications, 2026)
This study examines how an IKEA advertising campaign in Spain titled Efectos Colaterales (“Collateral Effects”) interacts with structural violence and socio-cultural peace in the country. For this investigation, we conduct a visual analysis on all four advertisements comprising Efectos Colaterales. While the campaign was found to effectively utilize humor and several other narrative techniques to portray a lifestyle adhering to the brand's identity, its storyline implicitly makes the customer solely responsible for attaining this aspirational lifestyle, thereby ignoring the institutional and socio-political realities that currently limit a substantial portion of the population's ability to obtain affordable housing. This article draws attention to the importance of studying truth claims embedded in everyday advertising and the ways in which these shape our construction and understanding of what a peace culture—or a lack thereof—could potentially look like.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas ::5311.01 Publicidad; ODS 12 - Producción y consumo responsables; peace culture; structural violence; IKEA; advertising; housing crisis; Spain